Aortopulmonary collateral flow quantification by MR at rest and during continuous submaximal exercise in patients with total cavopulmonary connection. Issue 6 (6th November 2017) - Mkrtchyan, Naira; Frank, Yvonne; Steinlechner, Eva; Calavrezos, Lenika; Meierhofer, Christian; Hager, Alfred; Martinoff, Stefan; Ewert, Peter; Stern, Heiko
Abstract : Background: Aortopulmonary collateral flow is considered to have significant impact on the outcome of patients with single ventricle circulation and total cavopulmonary connection (TCPC). There is little information on collateral flow during exercise. Purpose: To quantify aortopulmonary collateral flow at rest and during continuous submaximal exercise in clinical patients doing well with TCPC. Study Type: Prospective, case controlled. Population: Thirteen patients with TCPC (17 (11–37) years) and 13 age and sex‐matched healthy controls (18 (11–38) years). Field Strength: 1.5T; free breathing; phase sensitive gradient echo sequence. Assessment: Blood flow in the ascending and descending aorta and superior vena cava were measured at rest and during continuous submaximal physical exercise in patients and controls. Systemic blood flow (Qs ) was assumed to be represented by the sum of flow in the superior caval vein (Qsvc ) and the descending aorta (QAoD ) at the diaphragm level. Aortopulmonary collateral flow (Qcoll ) was calculated by subtracting Qs from flow in the ascending aorta (QAoA ). Statistics: Mann–Whitney U ‐test and Wilcoxon test for comparison between groups and between rest and exercise. Results: Absolute collateral flow in TCPC patients at rest was 0.4 l/min/m 2 (–0.1–1.2), corresponding to 14% (–2–42) of Qs . Collateral flow did not change during exercise (difference –0.01 (–0.7–1.0) l/min/m 2, P = 0.97). TCPC patients had significantly lower Qs at rest (2.5 (1.6–4.1) vs. 3.5 (2.6–4.8) l/min/m 2, P = 0.001) and during submaximal exercise (3.2 (2.0–6.0) vs. 4.8 (3.3–6.9) l/min/m 2, P = 0.001), compared to healthy controls. The increase in Qs with exercise was also significantly lower in patients than in healthy controls (median 0.6 vs. 1.2 l/min/m 2, P < 0.02). Data Conclusion: Clinical patients doing well with TCPC have significant aortopulmonary collateral flow at rest (14% of Qs ) compared to healthy controls, which does not change during submaximal exercise. Level of Evidence: 2 Technical Efficacy: Stage 3 J. Magn. Reson. Imaging 2018;47:1509–1516.